Yield losses in wheat genotypes caused by stripe rust (Puccinia striifarmis f. sp. tritici) in North Delta, Egypt ... : خسائر الغلة في الأنماط الجينية للقمح الناجمة عن الصدأ المخطط (Puccinia striifarmis f. sp. tritici) في شمال الدلتا، مصر ... - Yaser M. Hafez; Yasser S. A. Mazrou; A. Shahin; Farid Mehiar; M. Mehareb Eid; Khaled Abdelaal (OpenAlex, 2022)
Stripe (yellow) rust disease caused by Puccinia striifarmis f. sp. tritici, is a catastrophic wheat disease in wheat-growing regions around the world. The objective of this study was to investigate potential sources of stripe rust resistance and the yield loss of forty local wheat varieties at four locations in Egypt (Sakha, Mutubas, Qillin and Biyala), under yellow rust disease pressure compared to 'Morroco' variety, as control. To determine slow rusting in the field, the following parameters were recorded: final rust severity (FRS%), average coefficient of infection (ACI), relative resistance index (RRI) and reduction % in the 1000 kernel weight. The severity was higher in the second season than in the first. Seven wheat genotypes ('Shaka 62', 'Shaka 9, 'Shaka 95', 'Gemmiza 7', 'Sids 14' and 'Misr 3') showed the high level of resistance, and FRS% values ranged from 0 to 20 moderately resistant (MR) during first season and achieved the least value of loss in TKW (1.28%) with 'Misr 3'. Meanwhile, four ... : مرض الصدأ المخطط (الأصفر) الناجم عن Puccinia striifarmis f. sp. tritici، هو مرض قمح كارثي في مناطق زراعة القمح في جميع أنحاء العالم. كان الهدف من هذه الدراسة هو التحقيق في المصادر المحتملة لمقاومة الصدأ الشريطي وفقدان غلة أربعين نوعًا من القمح المحلي في أربعة مواقع في مصر (ساخا ومطوبس وقلين وبيالا)، تحت ضغط مرض الصدأ الأصفر مقارنة بصنف "المغرب"، كمكافحة. لتحديد الصدأ البطيء في الميدان، تم تسجيل المعلمات التالية: شدة الصدأ النهائية (FRS٪)، ومتوسط معامل العدوى (ACI)، ومؤشر المقاومة النسبية (RRI) ونسبة الانخفاض في وزن 1000 نواة. كانت الشدة أعلى في الموسم الثاني مما كانت عليه في الموسم الأول. أظهرت سبعة أنماط وراثية للقمح (" شاكا 62 "و" شاكا 9 "و" شاكا 95 "و" جيميزا 7 " و " سيديز 14 "و" مصر 3 ") مستوى عالٍ من المقاومة، وتراوحت قيم FRS٪ من 0 إلى 20 مقاومة معتدلة (MR) خلال الموسم الأول وحققت أقل قيمة للخسارة في TKW (1.28 ٪) مع "مصر 3". وفي الوقت نفسه، ظلت أربعة أنماط وراثية (' Sakha 93 'و' Sakha 95 'و' Sids 14 'و' Gim. 7 ') شديدة المقاومة خلال الموسم الثاني وتم تحديدها على أنها تتمتع بمستوى جيد من مقاومة الصدأ ...